Treatment of vinasse from tequila production using polyglutamic acid - Octavio, Carvajal-Zarrabal; Cirilo, Nolasco-Hipolito; Dulce, Barradas-Dermitz; Patricia M., Hayward-Jones; Guadalupe, Aguilar-Uscanga; Kopli, Bujang (2011)
Vinasse, the wastewater from ethanol distillation, is characterised by high levels of organic and inorganic matter, high exit process temperature (ca. 90 _C) and low pH (3.0e4.5). In this study, the treatment of tequila vinasse was achieved by a flocculationecoagulation process using poly-g-glutamic acid (PGA). Results showed that the use of PGA (250e300 ppm) combined with sodium hypochlorite and sand filtration managed to remove about 70% of the turbidity and reduced chemical oxygen demand (COD) by 79.5% with the extra benefit of colour removal. PGA showed its best flocculating activity at pH 2.5e3.5 and a temperature of 30e55 _C. Such a treatment may be a solution for small tequila companies for which other solutions to deal with their vinasse may not be economically affordable.